Die Matrikel der Wiener Rechtswissenschaftlichen Fakultät, II. Band: 1442-1557 - Matiasovits, Severin (2016)
This volume presents a critical edition of the register of the Faculty of Law at the University of Vienna between 1442 and 1557. This edition is made accessible with the aid of both a register of persons and a location register. The introduction contains amongst others a paleographic analysis of the various scribes of the registers, a statistical analysis and a prosopographical overview of the law students, a description of the conditions of studying and a short history of the Faculty of Law.